3D printable phantom for mimicking electrical properties of dermal tissue. Issue 7 (23rd February 2023) - Kuzemchak, Blake C.; Choe, Robert H.; Sherry, Mary; Porter, Emily; Fisher, John P.
Abstract: Skin cancer is one of the most ubiquitous forms of cancer that is often overdiagnosed or missed by traditional diagnostic techniques. Bioimpedance spectroscopy (BIS) is a technology that aims to take advantage of the variations in electrical properties of tissue to identify ectopic formations. It is difficult to develop BIS technologies without obtaining tumor tissue samples. One solution is to use a "tissue phantom, " a synthetic structure that mimics the properties of tissue. Current solutions using natural biomaterials, such as gelatin, have not been able to create complex tissue geometries that are vital to honing BIS diagnostics. However, semi‐synthetic polymers, such has gelatin methacrylate (GelMA), offer the benefits of possessing similar electrical properties to their respective source biomaterial while being 3D printable. In this work, we first measured the impedance of porcine dermal tissue. We then applied these impedance measurements to create an electrically accurate tissue phantom using a photocurable hydrogel, GelMA, and varying concentrations of NaCl, aluminum powder, and titanium dioxide powder.